TRANSFER OF INTELLECTUAL PROPERTY RIGHT AS A COMPANY ASSET IN BANKRUPTCY IN INDONESIA - Al Asy'arie, Moh. Asadullah Hasan; Rahmanda, Bagus; Prasetyo, Khanza Anindita (Diponegoro Law Review, 2024)
The transfer of intellectual property rights (IPR) as a company asset during bankruptcy proceedings in Indonesia presents a complex legal landscape. This study examines the gap between existing legal frameworks and the practical realities faced by companies undergoing bankruptcy. Specifically, the research addresses the lack of clear guidelines on the valuation, transfer, and protection of IP rights, which are critical assets in the modern economy. This  study  utilizes the three research methods, which are Normative Approach and Conceptual Approach. Findings indicate significant inconsistencies and ambiguities in the legal treatment of IPR in bankruptcy cases. The aim of this research is to provide an understanding of how IPR can be included in the bankruptcy estate and distributed to entitled creditors based on an assessment by the curator. In conclusion, this research found that recommendations for legal amendments and policy interventions to bridge the identified gaps, thereby enhancing the protection and transferability of IP rights in bankruptcy contexts in Indonesia.